Fides caritate formata. The Extreme Poles of the Baroque: Protestantism and Catholicism in Walter Benjamin’s Trauerspielbuch - Cruz Aponiuk, Juan (2025)
This paper provides a commentary on the Trauerspielbuch, Walter Benjamin’s rejected habilitation thesis. It aims to fill a significant gap in the reception of the text by highlighting a fact that has been systematically ignored: that the Baroque presented by Benjamin is characterized by two extreme poles in tension –a Protestant pole, which has been extensively commentated upon, and a Catholic pole, consistently silenced–. Likewise, this implies a reinterpretation of decisive Benjaminian themes: romanticism, capitalism as a religion, the allegorical, destiny, nakedness, melancholy, and sovereignty. If, in the posthumous fragment Kapitalismus als Religion, Benjamin diagnosed capitalism as a parasitic religion of Christianity, powerful enough to force Christianity to convert to capitalism through Protestantism, it will be in the Trauerspielbuch where he studies this conversion more closely. The signature of conversion is sola fide or naked faith, which plunges into greater desolation those who are more pious, as it leaves them without criteria to discern between the Kingdom and the Antikingdom, between salvation and damnation. Opposing it, through the baroque dialectical apotheosis, is the fides caritate formata that unites faith with works.